PENGARUH RETURN ON ASSETS, CURRENT RATIO, DEBT TO EQUITY RATIO DAN DIVIDEND PAYOUT RATIO TERHADAP HARGA SAHAM (Studi Empiris pada Perusahaan yang Tergabung Dalam Indeks LQ45 Di Bursa Efek Indonesia Periode 2016 – 2019) - Muhammad Wira Raspati; Welas Welas (Universitas Budi Luhur, 2021)
The purpose of this study was to determine the effect of return on assets, current ratio, debt to equity ratio, and dividend payout ratio on stock prices. The samples in this study are companies that are members of the LQ45 Index on the Indonesia Stock Exchange for the period 2016 - 2019. The sampling technique in this study uses the purposive sampling method, where there are 16 companies that are members of the LQ45 Index that meet predetermined criteria. This study uses multiple linear regression analysis methods using the Statistical Package for the Social Science (SPSS) program version 19.0 and Microsoft Excel for Windows 2007 to determine the effect of independent variables on the dependent variable. The results of this hypothesis testing indicate that the current ratio and debt to equity ratio have an effect on stock prices, while the return on assets and dividend payout ratio have no effect on stock prices.